BODIES OF KNOWLEDGE;BODIES OF KNOWLEDGE (AFRICAN SUN MEDIA, 2021)
Spanning the countries of South Africa, Swaziland, and Ghana, this collection of work brings into focus child and youth experience together as a collage of anthropology, creative writing, poetry, and the fine arts.